Liquid-vapor equilibrium and evaporation rate of Cd-Zn liquid alloy - Zhao, Weichen; Xu, B.Q; Yang, H.W (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
In this study, VLE (vapor-liquid equilibrium) data of cadmium-zinc system were determined at pressure of 7.5 Pa. We modeled VLE for Cd-Zn system in vacuum distillation using the Wilson equation. The results demonstrate that VLE phase diagram is reliable for predicting the process of vacuum distillation for Cd-Zn system. Evaporation rates of one element in Cd-Zn alloy were calculated by the Langmuir equation and were experimental measured. Experimental data on the evaporation of pure metals Cd and Zn are included. The evaporation coefficients of zinc and cadmium under vacuum conditions were calculated. The evaporation rates of zinc and cadmium in the alloy and pure metals Cd and Zn were calculated, respectively. The deviations were discussed. Comparing calculations with experimental results, it can be found that the trend is consistent. The activation energies of Cd and Zn in the Cd-Zn alloy under experimental conditions were also calculated.
Keywords: Cd-Zn alloy; Thermodynamic modeling; Kinetics; Evaporation rate; Vacuum distillation